REGULASI DIRI SEBAGAI MODERATOR DALAM HUBUNGAN FOMO DAN PENGGUNAAN MEDIA SOSIAL PADA SISWA SMA - Sofia, Sofia; Sahrani , Riana; Marella , Bianca (Provitae: Jurnal Psikologi Pendidikan, 2025)
The rapid advancement of technology and the internet makes it impossible for humans to be separated from using it. One of the developments used is social media. Social media is a collection of internet-based applications and interactions between users. Through social media we can share information and build social connections virtually. While it has benefits, it also brings challenges, such as the phenomenon of Fear of Missing Out (FoMO). FoMO is a fear experienced by individuals due to missing out on events that only other individuals have. The impact can be experienced by every individual so self-regulation is very necessary. Self-regulation is a behavior that helps to focus on achieving future goals. High school students are teenagers who are studying at a secondary level. Teenagers need to have self-regulation to be able to manage themselves to achieve their desired goals. This study aims to determine the role of self-regulation as a moderator in the relationship between FoMO and social media use in high school students. A quantitative study with 301 participants. The measuring instruments used were SMUQ, FoMOs, and SSRQ. The results show that FoMO has a positive relationship with social media use, with a p-value = 0.000 <0.05, which means that the higher the FoMO, the higher the use of social media. However, there is no role of self-regulation as a moderator in the relationship between FoMO and social media use in high school students because the MRA test p-value = 0.326 > 0.05.